Kyasanur Forest Disease in India: innovative options for intervention - Paramasivan Rajaiah (Taylor & Francis Group, 2019)
Kyasanur Forest Disease (KFD) is a tick-borne hemorrhagic fever of human, caused by Kyasanur forest disease virus (KFDV) in India. The tick, Haemaphysalis spinigera, has been incriminated as the vector of KFDV. In human, KFD clinically presents with high fever, frontal headache, and severe myalgia, followed by bleeding from the nasal cavity, throat, gingivae, and in some cases, gastrointestinal tract. The mortality rate in KFDV infected cases is estimated to be 3-10%. Monkeys infected with the virus also develop the disease and die. Though the incidence of KFD was found to be confined only to the sylvatic area of Shimoga district in Karnataka state in India during 1967, recent reports indicate its expanding potential to the neighboring states such as Kerala, Tamil Nadu, and Goa. The administration of an indigenous, inactivated tissue culture vaccine was found to drastically decrease the percentage of incidence; however, the recurrence of KFD in vaccinated subjects warrants innovative strategies for effective control of the infection. The present communication proposes and discusses innovative intervention strategies for the effective prevention and control of KFD in India.